Making the Modern Primitive Cultural Tourism in the Trobriand Islands - MacCarthy, Michelle (University of Hawaii Press, 2016)
Making the Modern Primitive provides an anthropological analysis of the encounter between local residents and tourists in the Trobriand Islands, a place renowned in anthropology and represented in various media as "culturally authentic." In such a place, how are ideas about authenticity implicated in creating and representing the self and cultural Others in the context of cultural tourism? Michelle MacCarthy addresses this question by examining four arenas of interaction between Trobriand Islanders and tourists: formal performances, informal village visits, souvenir shopping, and tourist photography. Drawing on both symbolic/interpretive approaches and concepts drawn from economic anthropology, she examines the relationship of tourism to the commoditization of culture, the ways in which local residents actively represent and enact "Trobriandness," and the ways tourists interpret and narrate their experience.